Perlindungan Hukum Debitur Atas Agunan yang Diambil Alih BPR Berdasarkan Asas Kepastian Hukum dan Itikad Baik - Eliakim Tinambunan; Roida Nababan; Sovia Simamora (Fakultas Hukum Universitas Riau, 2026)
Asset Takeover (AYDA) constitutes a non-performing loan resolution mechanism recognized in banking practice, including in Rural Credit Banks (BPR). Although normatively permitted, its implementation may raise legal concerns, particularly when collateral is taken over without the debtor’s consent and without proper execution of security rights as regulated by law. This study aims to analyze debtor legal protection against unilateral collateral takeover by a BPR, based on Jember District Court Decision Number 128/Pdt.Bth/2023/PN Jmr, and to examine the application of the principles of legal certainty and good faith in the AYDA mechanism. This research employs normative legal methods using statutory and case approaches. The results of the study show that the legal protection for debtors for collateral taken over by BPR without the debtor's consent is based on the Jember District Court Decision Number 128/Pdt.Bth/2023/PN Jmr and analyzes the application of the principle of legal certainty and the principle of good faith in the AYDA mechanism, especially in the obligation of creditors who act honestly and fairly towards the debtor during the collateral takeover process. In addition,, Such practice also fails to reflect the principle of good faith as mandated under Article 1338 paragraph (3) of the Civil Code. The court decision affirms that creditors’ preferential rights are not absolute and must be exercised in accordance with statutory provisions and justice principles. Therefore, AYDA implementation must ensure transparency, proportionality, and adherence to legal certainty and good faith.